Efficacy of atropine combined with paroxetine in vagus nerve excitatory panic disorder - Du, Na (Neuropsychiatr Dis Treat, 2015)
Panic disorder is often associated with the autonomic nervous system pattern – sympathetic activation and parasympathetic (vagal) withdrawal. However, we present one special case here to show a totally reversed pathogenesis – vagal activation occupying the leading role, which requires atropine to cure the patient’s symptoms. Through this report, it is reasonably proven that panic disorder may be a heterogeneous condition, whose mechanism might be the imbalance between the sympathetic and parasympathetic tone.